New species diversity and host association of Lactarius sect. Deliciosi: describing L. gibbosus and L. parvihatsudake (Russulaceae, Russulales) in southern China - Pu, Jin-Bao; Cao, Shu-Qin; Wang, Ran; Chen, Xia; Pang, Chun-Mei; Wang, Xiang-Hua (Phytotaxa, 2024)
Lactarius gibbosus and L. parvihatsudake, two red-colored species of Lactarius sect. Deliciosi are described as new from southern China. Lactarius gibbosus is a rare species, growing in fagaceous forest in southwestern China, similar to L. subindigo. Its pileipellis with slightly thick-walled swollen cells is unique in the section. The macrocystidia filled with golden yellow contents are another good character. This is the first report of red-colored species of L. sect. Deliciosi growing in fagaceous forest. Lactarius parvihatsudake grows in forest of Pseudolarix amabilis, an ancient relict Chinese tree only in eastern China. It has smaller basidiocarps and bigger spores than L. hatsudake. The discovery of this species added Pseudolarix to the potential host list of L. sect. Deliciosi. Phylogenetic analyses of the ITS region and glyceraldehyde-3-phophate dehydrogenase gene showed that L. gibbosus was a sibling of L. subindigo. These two species formed an early diverging lineage of L. sect. Deliciosi. Lactarius parvihatsudake was nested deeply in L. sect. Deliciosi but its closest relatives cannot be determined. These data update our understanding of the diversity of L. sect. Deliciosi in Asia and will hopefully help to understand the role of host shift in speciation of ectomycorrhizal fungi.